The tattooist of Auschwitz : a novel - Morris, Heather (Screenwriter) (Harper, an imprint of HarperCollinsPublishers, 2018)
"In April 1942, Lale Sokolov, a Slovakian Jew, is forcibly transported to the concentration camps at Auschwitz-Birkenau. When his captors discover that he speaks several languages, he is put to work as a Tätowierer (the German word for tattooist), tasked with permanently marking his fellow prisoners. Imprisoned for more than two and a half years, Lale witnesses horrific atrocities and barbarism--but also incredible acts of bravery and compassion. Risking his own life, he uses his privileged position to exchange jewels and money from murdered Jews for food to keep his fellow prisoners alive. One day in July 1942, Lale, prisoner 32407, comforts a trembling young woman waiting in line to have the number 34902 tattooed onto her arm. Her name is Gita, and in that first encounter, Lale vows to somehow survive the camp and marry her. A vivid, harrowing, and ultimately hopeful re-creation of Lale Sokolov's experiences as the man who tattooed the arms of thousands of prisoners with what would become one of the most potent symbols of the Holocaust, The Tattooist of Auschwitz is also a testament to the endurance of love and humanity under the darkest possible conditions"--